Managing job-related stress among child protection social workers in Egypt: The role of religion and social support - Sabala, Yasmine A (AUC Knowledge Fountain, 2019)
In order to better understand stress and coping among Egyptian child protection social workers, this study aimed to: 1) assess the levels of burnout, secondary trauma and compassion satisfaction they experience; 2) discover to what extent they relied on religion and social support to cope with stress; and 3) to see if religion and social support along with gender and years of experience explained levels of burnout, secondary trauma and compassion satisfaction. A total of 80 male and female child protection social workers who had varying years of experience were given scales that measured their overall job-related stress levels (measured by ProQOL, version 5) as well as their use of religious and emotional and instrumental social support coping strategies (measured by two scales from the COPE Inventory). In addition, participants listed the top three things they did when feeling work-related stress. It was found that child protection social workers exhibited average levels of job-related stress (burnout and secondary traumatic stress) and high levels of compassion satisfaction. It was also found that they used religious coping more than coping through emotional or instrumental social support. Gender and years of experience did not have a significant effect on use of the three types of coping strategies or on the levels of stress (burnout and secondary traumatic stress) or compassion satisfaction. To see if the coping strategies of instrumental social support, emotional social support and religion along with gender and years of experience were predictors of burnout, secondary traumatic stress and compassion satisfaction, multiple regression analyses were run. Results showed that only religion significantly predicted higher levels of burnout and only emotional social support significantly predicted higher levels of secondary trauma. It also showed that both religion and instrumental social support significantly predicted higher levels of compassion satisfaction. The implications of this research for reducing stress and supporting successful coping are discussed.